(untitled) (Global Journal of Human-Social Science, 2020)
Introduction-A 2009 national survey has shown that beer represents 60 precent of all alcohol consumed regularly in Brazil. It also shows that gender, education and urbanity make little difference to determinate people’s preference for beer. Its widespread consumption throughout the country permeates every social class and makes it seem "natural" choice. 2 Beer presence is so common in everyday life that people justify this consumption by arguing that it is not an alcoholic beverage. In fact, many think of it as a sort of refreshment, probably because it is served cold. Although physicians constantly warn about its alcoholic content, breweries lobby intensively to avoid restrictions on their propaganda message. Consequently, the consumption of beer has increased over the years. 3 [This chapter analyzes the increase of beer consumption as a consequence of early twentiethcentury temperance movements and industrialization. 4 I argue that the history of the industrial production of beer and its consumption in Brazil is closely related to temperance movements in several ways. First, temperance propaganda failed to convince consumers to quit alcohol. Second, temperance messages condemning both aguardente consumption and those who drank it helped to create a market for beer. 5 Third, the commercial strategies adopted by breweries were very successful.